Towards Maximising Hardware Resources and Design Efficiency via High-Speed Implementation of HMAC based on SHA-256 Design - Shamsiah, Suhaili; Norhuzaimin, Julai; Rohana, Sapawi; Nordiana, Rajaee (UPM Press, 2024)
Some applications, such as Message Authentication Code (MAC), rely on different hashing operations. There are various hash functions, including Message-Digest 5 (MD5), RACE Integrity Primitives Evaluation Message Digest 160 (RIPEMD-160), Secure Hash Algorithm 1 (SHA-1), and Secure Hash Algorithm 256 (SHA-256), among others. The network layer is the third of seven layers of the Open Systems Interconnection (OSI) concept, also known as the Internet. It handles network addressing and physical data routing. Nowadays, enhanced internet security is necessary to safeguard networks from illegal surveillance. As a result, Internet Protocol Security (IPsec) introduces secure communication across the Internet by encrypting and/or authenticating network traffic at the IP level. IPsec is an internet-based security protocol. Encapsulating Security Payload (ESP) and Authentication Header (AH) protocols are separated into two protocols. The MAC value is stored in the authentication data files of the Authentication Header and Encapsulating Security Payload. This article analyses a fast implementation of the Hash-based Message Authentication Code (HMAC), which uses its algorithm to ensure the validity and integrity of data to optimise hardware efficiency and design efficacy using the SHA-256 algorithm. During data transfer, HMAC is critical for message authentication. It was successfully developed using Verilog Hardware Description Language (HDL) code with the implementation of a Field Programmable Gate Array (FPGA) device using the Altera Quartus II Computer-Aided Design (CAD) tool to enhance the maximum frequency of the design. The accuracy of the HMAC design, which is based on the SHA-256 design, was examined and confirmedusing ModelSim. The results indicate that the maximum frequency of the HMAC-SHA-256 design is approximately 195.16 MHz.